Recent Progress in Neuromorphic Computing from Memristive Devices to Neuromorphic Chips - Yike Xiao; Cheng Gao; Juncheng Jin; Weiling Sun; Bowen Wang; Yukun Bao; Chen Liu; Wei Huang; Hui Zeng; Yefeng Yu (Advanced Devices & Instrumentation)
Neuromorphic computing, drawing inspiration from the brain, stands out for its high energy efficiency in executing complex tasks. Memristive device-based neuromorphic computing has demonstrated ultrahigh efficiency. While there are numerous review papers in this field, the majority concentrate on the device level, bypassing the connections among the performance metrics of memristive devices and those of neuromorphic chips. In this review, we investigate the recent progress in neuromorphic computing from the fundamental memristive devices to the intricate neuromorphic chips, highlighting their links and challenges.